2004
DOI: 10.2202/1949-6605.1390
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of New Student Campus Recreation Centers

Abstract: OThe student recreation center (SRC) at many colleges and universities has evolved from being a place to lift weights and take aerobics classes to becoming a high-powered recruitment tool (Colleges use recreation, 2002). The present study included the development of an instrument to assess the use and impact of SRCs. Students (N = 655; users = 537, nonusers = 118) were surveyed about their use of and satisfaction with their university's newly constructed SRC. The overall findings revealed that a majority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Over the past 35 years, several studies have reported evidence of positive relationships among persistence and campus facilities (e.g., libraries, labs, residence halls, classrooms), college choice, student satisfaction, and identification with the institution (Astin, 1973;Cain & Reynolds, 2006;Churchill & Iwai, 1981;Mallinckrodt & Sedlacek, 1987;Webster & Sedlacek, 1982;Zizzi, Ayers, Watson, & Keeler, 2004). As one would expect, academic facilities were reported by students to be of key importance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the past 35 years, several studies have reported evidence of positive relationships among persistence and campus facilities (e.g., libraries, labs, residence halls, classrooms), college choice, student satisfaction, and identification with the institution (Astin, 1973;Cain & Reynolds, 2006;Churchill & Iwai, 1981;Mallinckrodt & Sedlacek, 1987;Webster & Sedlacek, 1982;Zizzi, Ayers, Watson, & Keeler, 2004). As one would expect, academic facilities were reported by students to be of key importance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To ensure a positive connection with student success, the availability of recreational programming data is key for institutional recruitment and retention efforts (Kampf & Teske, 2013). In addition, the need for research in areas of recreation facility usage and social and learning outcomes is well-documented (Zizzi et al, 2004).…”
mentioning
confidence: 99%
“…Lindsey and Sessoms (2006) found that female students were more likely to participate in campus recreational sports, while juniors and seniors consider these campus recreational programs as an important indicator of college selection. In contrast, some past research (Barcelona & Ross, 2002;Terzioğlu & Yazıcı, 2003;Young et al, 2003;Zizzi et al, 2004;Balcı & İlhan, 2006;Tekin et al, 2007;Miller et al, 2008;Lindsey et al, 2009;Lindsey, 2012;de Jager & Gbadamosi, 2013) found that male students were more likely to be participants and other earlier studies (Watson II et al, 2006;Miller et al, 2008;Milton & Patton, 2011) showed that lower-division students (freshmen and sophomores) were more likely to participate in campus recreational facilities. However, earlier research (Shank & Beasley, 1998;Frauman, 2005;Clemes et al, 2008;Sökmen, 2011;Moosmayer & Siems, 2012) indicated that there were no differences in the perceived importance of quality of campus life facilities with respect to students' gender.…”
Section: Review Of Related Literaturementioning
confidence: 88%